Besarnya Tegangan Longitudinal Dan Tegangan Tangensial Yang Terjadi Pada Dinding Bejana Bertekanan Di Unit BPV (Back Pressure Vessel) Akibat Adanya Tekanan Fluida Dari Dalam Pada PT. XYZ - Yanto Yanto; Mhd Anas Hafidz Setiawan (CV MEDAN TEKNO SOLUSI, 2023)
This research was carried out on a BPV (Back Pressure Vessel) unit where there are voltages acting within the pressure vessel which are capable of causing dimensional changes to the pressure vessel due to pressure. Pressure vessels can accommodate a wide range of elements covering several applications such as in the nuclear, oil, chemical industries, and oil and gas. With research methods carried out at the research site or carrying out field research activities. There are two ways of collecting this data, namely the interview method, which is a way of collecting data by holding interviews or direct questions and answers with heads of departments or company employees about BPV (Back Pressure Vessel) units. Observation Method, namely a method of collecting data by means of direct observation in the field of the object to be carried out carefully. The longitudinal stress that occurs is 158.13909 MPa and the tangential stress that occurs is 23.222 MPa for a working pressure of 3.2 Kg/cm2.